City Planning Labs : A Concept for Strenghtening City Planning Capacity in Indonesia - The City Form Lab (World Bank, Washington, DC, 2015)
The cities that emerge from Indonesia s rapid urbanization will be key determinants of the country s overall economic development and competitiveness, as well as their inclusiveness and environmental sustainability. However, without strategically planned investments, policy interventions, and institutional capacity, mismanaged urbanization could become an obstacle to sustainable growth. The city planning labs core module will be initially implemented in four cities: Surabaya, Palembang, Denpasar and Balikpapan, with two additional modules in each city. In the short term, the CPL will: (i) provide just in time , demand driven data and analysis that can feed into immediate decisions, and (ii) streamline ongoing urban management functions, such as building permitting and tax-related functions. In the medium term, it will provide cost-effective analytics to cities that can feed into planning and investment decisions, reducing the expense involved in contracting consultants during each planning cycle. In the long term, the CPL will build local technical capacity, by gathering expertise from Indonesia and international sources to work closely with local staff. Over time, external involvement will diminish as local capacity strengthens. The activities of the CPL will be conducted in modular fashion, each pertaining to a different sector. The sector modules are: instituting the city planning lab and spatial growth analytics (core module); city economic competitiveness; slum analytics and management systems; climate and risk resilience planning systems; and monitoring land and real estate markets.